0670 Sleep-Related Event Physiologic Timing for Triggering Nonsustained Ventricular Tachycardia: A Case-crossover Analysis. (12th April 2019) - May, Anna M; May, Ryan D; Bena, James; Wang, Lu; Monahan, Ken; Stone, Katie L; Barrett-Connor, Elizabeth; Koo, Brian B; Winkelman, John W; Redline, Susan; Mittleman, Murray A; Mehra, Reena
Abstract: Introduction: Periodic limb movements during sleep (PLMS) with arousal and respiratory events are associated with arrhythmogenesis, however, intervals of heightened vulnerability are unclear. We conducted an exploratory investigation to ascertain temporal sleep-related event-nonsustained ventricular tachycardia (NSVT) associations. Methods: Temporal sleep-related event and NSVT associations in 41 Osteoporotic Fractures in Men Sleep Study participants with in-home polysomnography-identified NSVT during sleep were examined via a bidirectional case-crossover design. For each blindly-annotated NSVT event (n=96), we selected a preceding hazard period (HP) and three randomly-chosen 30-second control periods from sleep at ~5-minute intervals from NSVT within the same 30-minute segment and evaluated for PLMS, respiratory events, and arousals. Univariate conditional logistic regression determined odds ratios (OR) and 95% confidence intervals. Induction time, defined as time between a sleep-related event ending and NSVT initiation, was assessed in 2 ways: (1) varying HP duration 10-150 seconds and (2) timing the 30-second HP start earlier relative to the NSVT event. OR significantly different from 1 defined the induction period. Results: PLMS with arousals (PLMA), arousals, and PLMS-related arousals were associated with NSVT in male participants (79.8±6.0 years, PLMS index of 40.6 [IQR: 21.6, 67.1], apnea-hypopnea index of 17.1 [IQR: 8.6, 26.1]). The HP duration associated with NSVT based on significant OR was 15-70 seconds for PLMA, 140 seconds for arousal, and bimodal for PLMS-related arousals (0-58 and 119-121 seconds). Based on the timing analysis, NSVT was associated with PLMA at 0-51 and 169-219 seconds and PLMS-related arousals at 0-48 and 160-219 seconds. PLMS, non-PLMS-related arousals, respiratory-related arousals, and respiratory events were not significantly associated with NSVT. Conclusion: This exploratory study suggests that PLMA and PLMS-related arousals trigger NSVT, PLMS-related arousals have a bimodal physiologic effect, and NSVT episodes are more strongly associated with PLMA than respiratory events in older men. Support (If Any): Osteoporotic Fractures in Men (MrOS) Study: U01-AG027810, U01-AG042124, U01-AG042139, U01-AG042140, U01-AG042143, U01-AG042145, U01-AG042168, U01-AR066160, and UL1- TR000128. MrOS Sleep ancillary study: R01-HL071194, R01-HL070848, R01-HL070847, R01-HL070842, R01-HL070841, R01-HL070837, R01-HL070838, R01-HL070839, and R21-HL108226. Dr. May: NHLBI T32-HL007913 and ATS ASPIRE Fellowship.